Agri-tourism: potential opportunities for farmers an local communities in Malaysia - Tiraieyari, Neda; Hamzah, Azimi (Academic Journals, 2012)
This article reviewed literature on potential benefits of agri-tourism for farmers and local communities in general. It also provided a review of agri-tourism development, particularly in Malaysia. Reviewing literature indicated that agri-tourism as an economic development instrument has great potential to contribute to rural development. Malaysia is one of the tourist countries with great potential to develop agri-tourism. Agricultural areas in this country have many tourist attractions which can form the basis for relaxation, enjoyment and education of tourist. Although this country has existing base of agri-tourism attractions, its potential for agri-tourism is far greater. It is suggested that to improve the economic, social and environmental situation of rural communities in Malaysia, the department of agriculture as well as universities should give orientation towards agri-tourism by providing some innovative ideas suitable for each region. It is also recommended that tourism industry should make stronger links with agriculture to make agri-tourism continue the tourism trend in Malaysia.